Peran Koperasi Ramah Keluarga Bali Membangun Sinergi Untuk Energi Pang Pada Payu - Rai Wahyuni, Anak Agung Ayu; Dewi Setiowati Sunaryo, Fransiska (Humanis, 2023)
The role of cooperatives in people's lives in Indonesia, especially in Bali, is very influential in maintaining the economy, especially during a pandemic in Bali. One of the unique cooperatives in Bali is the Bali Family Friendly Women's Cooperative, hereinafter referred to as KPRK Bali in building optimism and adapting to new habits in building markets due to the Covid-19 pandemic that occurred in Bali. Facing the new era, it is imperative that cooperatives and MSME actors carry out transformation, in addition to facilitating the use of technology in the information sector, as well as protecting business actors and consumers from the impact of Covid-19. The purpose of writing this article is to find out the role of the Bali KPRK Cooperative in promoting local wisdom with the tag line Pang Pada Payu Bali. KPRK Bali considers it important to encourage environmentally friendly economic activities with the principles of a sustainable economy. The issues raised included: What is the role of KPRK Bali in driving the Bali economy? How is the implementation of KPRK Bali management? and What are the benefits obtained by KPRK members and the people of Bali?